Large tumor suppressor 2, LATS2, activates JNK in a kinase-independent mechanism through ASK1. (29th November 2018) - Rusnak, Lauren; Tang, Cong; Qi, Qi; Mo, Xiulei; Fu, Haian
Abstract: Apoptosis signal-regulating kinase 1 (ASK1) is an important mediator of the cell stress response pathways. Because of its central role in regulating cell death, the activity of ASK1 is tightly regulated by protein–protein interactions and post-translational modifications. Deregulation of ASK1 activity has been linked to human diseases, such as neurological disorders and cancer. Here we describe the identification and characterization of large tumor suppressor 2 (LATS2) as a novel binding partner for ASK1. LATS2 is a core kinase in the Hippo signaling pathway and is commonly downregulated in cancer. We found that LATS2 interacts with ASK1 and increases ASK1-mediated signaling to promote apoptosis and activate the JNK mitogen-activated protein kinase (MAPK). This change in MAPK signaling is dependent on the catalytic activity of ASK1 but does not require LATS2 kinase activity. This work identifies a novel role for LATS2 as a positive regulator of the ASK1–MKK–JNK signaling pathway and establishes a kinase-independent function of LATS2 that may be part of the intricate regulatory system for cellular response to diverse stress signals.